NewProt – a protein engineering portal. Issue 6 (5th May 2017) - Schwarte, Andreas; Genz, Maika; Skalden, Lilly; Nobili, Alberto; Vickers, Clare; Melse, Okke; Kuipers, Remko; Joosten, Henk-Jan; Stourac, Jan; Bendl, Jaroslav; Black, Jon; Haase, Peter; et al.
Abstract: The NewProt protein engineering portal is a one-stop-shop for in silico protein engineering. It gives access to a large number of servers that compute a wide variety of protein structure characteristics supporting work on the modification of proteins through the introduction of (multiple) point mutations. The results can be inspected through multiple visualizers. The HOPE software is included to indicate mutations with possible undesired side effects. The Hotspot Wizard software is embedded for the design of mutations that modify a proteins' activity, specificity, or stability. The NewProt portal is freely accessible at http://newprot.cmbi.umcn.nl/ and http://newprot.fluidops.net/ .